PENINGKATAN KUALITAS BIBIT PISANG KEPOK MELALUI RADIASI SINAR GAMMA SECARA IN VITRO - Astutik Astutik (BUANA SAINS, 2009)
This research was aimed at understanding and examining plantlet response to Kepok Banana in various doses of gamma ray radiation. Single Complete Random Planning was employed with 5 levels of gamma ray radiation doses. These five treatments comprised to 0 krad (A); 2.5 krad (B); 5.0 krad (C); 7.5 krad (D); and 10.0 krad (E). Every treatment had 5 replications. Each replication had 2 bottles such that 50 bottles emerge for a unit of experiment. The observation involved parameters such as shooting period, number of shoot, number of leaf, shoot height, plantlet stem, rooting period, number of leaf chlorophyll, and esterase iso enzyme tape pattern. Results of research indicated that gamma ray radiation doses affected its morphology characteristics (shooting period, number of shoot, number of leaf, shoot height, and number of leaf chlorophyll) and its genetic characteristics (esterase iso enzyme tape pattern from leaf). Dose of 2.50 krad gamma ray was able to produce mutant-based Kepok Banana shown by different morphology and genetic characteristics from original seed. Doses of 5.0, 7.5, and 10.0 krad gamma ray radiations had harmful effect on plantlet of Kepok Banana